2012
DOI: 10.1177/0267658312447612
|View full text |Cite
|
Sign up to set email alerts
|

Clitic-doubled left dislocation and focus fronting in L2 Spanish: A case of successful acquisition at the syntax–discourse interface

Abstract: This experimental study tests the Interface Hypothesis by looking into processes at the syntax–discourse interface, teasing apart acquisition of syntactic, semantic and discourse knowledge. Adopting López’s (2009) pragmatic features [±a(naphor)] and [±c(ontrast)], which in combination account for the constructions of dislocation and fronting, we tested clitic left dislocation and fronted focus in the comprehension of English native speakers learning Spanish. Furthermore, we tested knowledge of an additional se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 37 publications
(50 reference statements)
7
72
1
1
Order By: Relevance
“…The acquisition of Ø topic provides further evidence to the claim that some aspects at the syntax-discourse external interface are acquirable (Ivanov 2012;Iverson et al 2008;Kraš 2008;Rothman 2007Rothman , 2009Slabakova et al 2012;Slabakova and Ivanov 2011;Zhao 2008Zhao , 2012a. The current study supports the proposals of White (2011) andYuan (2010) that interface vulnerability may not be domain-wide in that Ø topic at the syntax-discourse interface is acquired in comparison with some syntax-discourse properties that have proved to be vulnerable to ultimate fossilisation as discussed in Sorace and Filiaci (2006), among others.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The acquisition of Ø topic provides further evidence to the claim that some aspects at the syntax-discourse external interface are acquirable (Ivanov 2012;Iverson et al 2008;Kraš 2008;Rothman 2007Rothman , 2009Slabakova et al 2012;Slabakova and Ivanov 2011;Zhao 2008Zhao , 2012a. The current study supports the proposals of White (2011) andYuan (2010) that interface vulnerability may not be domain-wide in that Ø topic at the syntax-discourse interface is acquired in comparison with some syntax-discourse properties that have proved to be vulnerable to ultimate fossilisation as discussed in Sorace and Filiaci (2006), among others.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are not fully consistent with the predictions of the IH, but this study is not the only one that has produced findings inconsistent with the IH. The non-acquisition of narrow syntactic properties is also found in Coppieter (1987), Sorace (1993) and Kraš (2011), while the acquirability of the syntax-discourse interface categories are consistent with Ivanov (2012), Iverson et al (2008), Kraš (2008), Rothman (2007), Slabakova et al (2012, Slabakova and Ivanov (2011) and Zhao (2008Zhao ( , 2012a. This study provides supporting evidence to the claim that the (non-)acquirability of a particular interface cannot be generalised (White 2011;Yuan 2010).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Given that we wanted to provide an equivalent contrast to previous testing materials (Slabakova et al 2011, Slabakova et al 2012, we presented the choices (felicitous vs. infelicitous) simultaneously, as was done in our previous investigations. While this was done in the interest of avoiding test fatigue, we acknowledge that a better presentation mode (especially for the L1-dominant native speakers)…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research has documented similar asymmetries with respect to other linguistic phenomena (Belletti & Leonini, 2004;Lozano, 2006;Valenzuela, 2006). However, other empirical studies have either failed to detect any apparent signs of instability in domains predicted by the Interface Hypothesis to be vulnerable or suggested that such interface-related difficulties are not pervasive (Donaldson, 2011(Donaldson, , 2012Ivanov, 2012;Iverson, Kempchinsky, & Rothman, 2008;Leal Méndez, Rothman, & Slabakova, in press;Slabakova & Ivanov, 2011;Slabakova, Kempchinsky, & Rothman, 2012). Researchers have also challenged some aspects of the hypothesis on theoretical grounds, including the imprecise formulation of the proposal, difficulty of distinguishing interface-related phenomena from noninterface-related phenomena (and, by the same token, external interfaces from internal interfaces), difficulty of positioning the hypothesis within specific theoretical models of language architecture, and potentially an overly "restrictive" focus of the proposal, originally formulated only for some bilingual populations and not others (Domínguez, 2013;Montrul, 2011;Rothman, 2009;Rothman & Slabakova, 2011;White, 2011).…”
Section: Interfaces: the Integration Problemmentioning
confidence: 95%